THE EFFECT OF TAXATION ADMINISTRATION REFORM AND TAXATION KNOWLEDGE ON COMPLIANCE OF VAT ENTERPRISES - Abdul Hafiz Tanjung (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2020)
This research aims to give an overview about taxation administration reform, taxtation knowledge and compliance taxable enterpreneur for VAT purposes descriptively, and whether there is or not an influence of taxation administration reform and taxtation knowledge towards compliance taxable enterpreneur for VAT Purposes on KPP Pratama Cibeunying Kaler. Data used in this research was primer data collected by using questionnaire which was distributed to respondents. Respondent in this research is VAT Enterprises listed on KPP Pratama Cibeunying Kaler. Amount of samples obtained as many as 49 VAT Enterprises taken by method Simple Random Sampling from 96 VAT Enterprises as a population. As for the research method used was descriptive method and associative. While the data analysis method is in this research is Multiple Linear Regression Analysis. The result of this research shows that taxation administration reform and taxtation knowledge both partially and simultaneously positive and significant effect to compliance Taxable Enterpreneur for VAT Purposes on KPP Pratama Cibeunying Kaler.